Bridging Gaps: Enhancing Holistic Mathematics Support in the Transition from Secondary School to University - Alfred Msomi; Ekaterina Rzyankina (Journal of Student Affairs in Africa)
The provision of multidimensional holistic mathematics support for students transitioning from secondary school to university level is identified as a challenge currently facing global education systems including in South Africa. Ongoing attempts to select effective mathematics learning support reflect the enduring nature of a problem with multifaceted contributing factors. Despite a wealth of literature there has been little effort to consolidate diverse sources into a comprehensive and useful understanding. This study aims to close this gap by synthesising and integrating these disparate elements into a unified framework. The research employs a comprehensive rapid literature review, meticulously following the PRISMA guidelines. The review concentrates on papers which investigate the impact of specific types of mathematical support, on those conducting analyses of the efficacy of distinct mathematical support approaches, and papers proposing solutions towards improving first-year South African university students’ mathematics performance. To mitigate bias, the Rayyan AI-assisted literature review platform is utilised, ensuring a rigorous and unbiased selection process. This rapid literature review reveals a general hindrance to holistic mathematics learning support, in the form of an absence of a unified framework. We see this deficiency as potentially detrimentally impacting students, and as underscoring the need for a comprehensive approach. The findings suggest that mathematics support can be enhanced by integrating the core elements of a holistic approach, together with acknowledging the interconnectedness and mutual influence of the various elements.